2013
DOI: 10.1111/odi.12095
|View full text |Cite
|
Sign up to set email alerts
|

Malignant transformation of oral leukoplakia in a well‐defined cohort of 144 patients

Abstract: Objectives Oral leukoplakia is a potentially malignant disorder of the oral mucosa. The aim of this retrospective study was to identify the factors that possibly predict malignant transformation in a well‐defined cohort of patients with a long‐term follow‐up. All leukoplakias were staged according to a clinicopathological classification and staging system. Furthermore, a certainty factor has been used with which the diagnosis has been established. Material and methods The group consisted of 144 patients. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
145
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(163 citation statements)
references
References 36 publications
14
145
3
1
Order By: Relevance
“…Several treatments have been suggested in the literature, including surgery, electrosurgery, cryosurgery, topical agents (bleomycin, vitamin A), systemic agents (b-carotene, lycopene, retinoids), CO 2 laser and photodynamic treatment, although surgery and CO 2 laser are most frequently used. There is still no evidence that treatment prevents malignant transformation, although it seems advisable to treat oral leukoplakia with or without dysplasia (Horch et al, 1986;Chandu and Smith, 2005;Van der Waal, 2009;Santos et al, 2010;Yang et al, 2011;Song and Franco, 2011;Brouns et al, 2014) Q1 . 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 New technologies and improvements in oral and maxillofacial surgery and especially in laser surgery prove less invasive and more comfortable for patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several treatments have been suggested in the literature, including surgery, electrosurgery, cryosurgery, topical agents (bleomycin, vitamin A), systemic agents (b-carotene, lycopene, retinoids), CO 2 laser and photodynamic treatment, although surgery and CO 2 laser are most frequently used. There is still no evidence that treatment prevents malignant transformation, although it seems advisable to treat oral leukoplakia with or without dysplasia (Horch et al, 1986;Chandu and Smith, 2005;Van der Waal, 2009;Santos et al, 2010;Yang et al, 2011;Song and Franco, 2011;Brouns et al, 2014) Q1 . 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 New technologies and improvements in oral and maxillofacial surgery and especially in laser surgery prove less invasive and more comfortable for patients.…”
Section: Introductionmentioning
confidence: 99%
“…At a workshop coordinated by the WHO in 2005, "potentially malignant disorder" was the preferred terms, with the working group agreeing that the term leukoplakia should be used to recognize "white plaques of questionable risk having excluded (other) known diseases or disorders that carry no increased risk for cancer" (Warnakulasuriya et al, 2007). Prevalence of oral leukoplakia is reported to be approximately 2% (Petti, 2003;Brouns et al, 2013aBrouns et al, , 2013b and the annual malignant transformation rate is estimated to be between 0.13% and 17.5% (Deppe et al, 2012;Kumar et al, 2013;Brouns et al, 2014). Leukoplakia is considered to be the most common premalignant lesion of the oral cavity; its occurrence is related to smoking, with alcohol as an independent factor.…”
Section: Introductionmentioning
confidence: 99%
“…Malignant transformation rates for leukoplakia lesions are variable, depending on the sample selection and the follow-up time; Lončar-Brzak et al [14], have reported among 139 leukoplakia lesions, malignant evolution rate on a 10-year follow-up period was 0.64%. More recently, Brouns et al [5] reported a malignant transformation rate for leukoplakia lesions of approximately 2.6% among 144 lesions studied on a 51-month follow-up period. Although leukoplakia malignant transformation rates are apparently lower when compared to erythroplakya lesions malignant potential [29] the risk for malignant evolution is clear, therefore, patients diagnosed with leukoplakia lesions during this campaign will have adequate clinical followup, and, if necessary, therapeutic approach will be performed.…”
Section: Discussionmentioning
confidence: 99%
“…And although most of them are small with short follow up, retrospective in nature and biased, i.e. unable to provide sound (and even notso-sound) evidence, the results of some of the best did not show significant benefits of surgical treatment [3][4][5].…”
mentioning
confidence: 99%
“…A treatment that is useless in nine time out of ten should be, at least, absolutely safe. Something that is not true for a number of medical treatment proposed [6], and probably for surgery, particularly for large lesions (which, by the way, are those at higher risk) [4,5,7].…”
mentioning
confidence: 99%